Examining the effect of a sexual self-efficacy based educational intervention on postmenopausal sexual satisfaction and sexual distress: a parallel quasi-experimental study - Ata Torkamani; Mansoureh Jamshidimanesh; Sally Pezaro; Elahe Amirkhalili (BMC Women's Health)
Abstract Objective Menopause is associated with changes that affect sexual functioning. We evaluated the effect of a sexual self-efficacy-based educational intervention on postmenopausal sexual satisfaction and distress. Methods A parallel quasi-experimental study was conducted with participants (n = 70) consisting of postmenopausal women and their spouses from six health centers in Qom, Iran. Convenience sampling was used to recruit eligible individuals, who were then randomly assigned to an intervention group (n = 35 couples) and a control group (n = 35 couples). Those in the intervention group received six 90-minute weekly sessions while the control group received a single educational nutrition and physical activity session. Demographic data were collected alongside data collected via Index of Sexual Satisfaction and Female Sexual Distress Scale. Questionnaires were completed before the intervention, immediately afterward, and two months post-intervention. The data was analyzed by independent sample t-test, ANOVA, and two-way ANOVA repeated measures. Results There were no significant difference in sexual satisfaction between the two groups. Using repeated measures analysis, the group effect and time effect were not significant difference, but the interaction between group effect and time effect was significantly difference (p = 0.032). Sexual self-efficacy based educational intervention could just change mean score in intervention group. Sexual distress also did not differ significantly between the two groups. However, differences in the time effect were statistically significant (P < 0.001). Conclusion This educational intervention did not significantly impact the sexual distress of postmenopausal women. Nevertheless, longer follow-up periods and larger sample sizes are recommended and may yield more significant results. Clinical trial registration The study was registered in the Thai Clinical Trials, Registry TCTR20200213002. Registered on 10/01/2020.